1981
DOI: 10.1093/nar/9.22.6191
|View full text |Cite
|
Sign up to set email alerts
|

Is Tb3+fluorescence enhancement only due to binding to single stranded polynucleotides?

Abstract: Enhancement of Tb3+ fluorescence upon binding to double-stranded ribo- and deoxyribo-duplexes was investigated. It was observed that certain double stranded ribopolynucleotides completely quenched the Tb3+ fluorescence and others did not. It is concluded that the nature of the base in the duplex is critical for this enhancement. - Polydeoxyduplexes also showed enhancement of Tb3+ fluorescence, but much higher terbium concentrations were necessary to obtain similar fluorescence signals, indicative of unspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Also, a given cation may have very different effects on different systems. It was shown (28) that Th ions are very efficient at 10 5 M to induce the Z form in poly(dG-dC)&poly(dG-dC), in poly(dA-dC).poly(dG-dT)they cause a decrease of the CD spectrum similar to that in fig. 3,a.…”
Section: Discussionmentioning
confidence: 60%
“…Also, a given cation may have very different effects on different systems. It was shown (28) that Th ions are very efficient at 10 5 M to induce the Z form in poly(dG-dC)&poly(dG-dC), in poly(dA-dC).poly(dG-dT)they cause a decrease of the CD spectrum similar to that in fig. 3,a.…”
Section: Discussionmentioning
confidence: 60%
“…Haertle et al [15] have shown recently that in low salt aqueous medium (pH 6) Tb(III) induces the B-+Z transition in poly(dG-dC), with enhancement of the fluorescence intensity. However, no further analysis of the left-handed CD pattern in the presence of Tb(III) has been attempted here.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the induced fluorescence intensity of Tb(II1) in the later case, is dramatic, and an order of magnitude higher than that of the Tb(III)-right handed DNA complex. By analyzing the CD spectral change induced by Tb(lII) on poly(dG-dC) in aqueous medium [15] i.e. from the ratio of the positive to negative ellipticities, it appears that Tb(III)-poly(dG-dC) may not be in the exact lefthanded DNA configuration, but rather is represented by some intermediate form.…”
Section: Discussionmentioning
confidence: 99%
“…Because each phosphate group of the DNA molecules, carrying one "effective" negative charge, is neutralized by Gd 3+ ion [20], which carries three positive charges, this means that the altered surface charge distribution makes an additional contribution to the chiral interaction between adjacent (ds DNA-Gd 3+ ) complexes in the particles [21,22]. In this case one can expect that the pitch of the spatial twist of cholesteric structure formed by the ds DNA is changed as a result of interaction of Gd 3+ ions with these molecules [17].…”
Section: Salting-out Of Dna Molecules Inside Clcd Particlesmentioning
confidence: 99%